Effect of Composite Color and Thickness on Correction of Tooth Discoloration - Ghassemi, Amir; Emamieh, Shila; Soroudi, Aydin; Torabzadeh, Hassan; Akhavan Zanjani, Vaghareddin; Abdo Tabrizi, Maryam; Akbarzadeh Bagheban, Alireza (Journal of Dental School, 2019)
Objective: Selection of an appropriate shade of composite is critical in achieving an esthetic restoration. Different systems are used to assess and describe color parameters. This study aimed to assess the effect of color and thickness of Filtek Supreme (FS) and Premise (P) composite resins on correction of tooth discoloration. Methods: In this in vitro experimental study, 10 anterior teeth with Vita A2 color shade were selected. Composite specimens were fabricated in 0.5 and 0.75 mm thicknesses of FS and P composites. Intact teeth, prepared teeth, prepared teeth with enamel and dentin composite discs on their buccal surfaces, stained teeth and stained teeth with composite discs were photographed using a digital camera under standard conditions and color change (ΔE) at different phases was calculated. Results: The L*, a* and b* color parameters in prepared and unstained teeth were not significantly different from those of intact teeth. In stained teeth, the L* parameter only in prepared and stained teeth with 0.75mm P composite was not significantly different from the L* parameter in intact teeth. Significant differences were seen in other stained teeth. The a* and b* parameters only in prepared and stained teeth with 0.5 mm FS composite were significantly different from those in intact teeth. By increasing the thickness of composite, the color change in comparison with intact teeth decreased in both groups. Conclusion: The results showed that the effect of type of composite, its thickness and their interaction on the color change was significant when using FS and P composites in 0.5 and 0.75mm thicknesses in comparison to intact teeth and the lowest color difference with intact teeth was achieved using 0.75mm thickness of P composite (enamel and dentin).